2010
DOI: 10.4049/jimmunol.0902051
|View full text |Cite|
|
Sign up to set email alerts
|

Stimulation of FcγRI on Primary Sensory Neurons Increases Insulin-Like Growth Factor-I Production, Thereby Reducing Reperfusion-Induced Renal Injury in Mice

Abstract: Biological role(s) of FcγRI on mouse primary sensory neurons are not fully understood. Sensory neuron stimulation increases insulin-like growth factor-I (IGF-I) production, thereby reducing ischemia/reperfusion (I/R)-induced tissue injury in mice. In this study, we examined whether the Fc fragment of IgG (IgGFc) increases IGF-I production through sensory neuron stimulation, thereby reducing I/R-induced renal injury in mice. IgGFc increased the calcitonin-gene–related peptide (CGRP) release and cellular cAMP le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A previous study also demonstrated that the activation of FcγRI by the Fc fragment of IgG (IgG Fc) at the higher dose induced smaller changes in CGRP release and cAMP levels in DRG neurons, as compared to the lower dose of IgGFc (Harada et al, 2010). One possible reason is that the higher concentration of IC mixtures contain a relative larger amount of monometric IgG that competitively blocks the effects of FcγRI on the neuronal surface (Nimmerjahn and Ravetch, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…A previous study also demonstrated that the activation of FcγRI by the Fc fragment of IgG (IgG Fc) at the higher dose induced smaller changes in CGRP release and cAMP levels in DRG neurons, as compared to the lower dose of IgGFc (Harada et al, 2010). One possible reason is that the higher concentration of IC mixtures contain a relative larger amount of monometric IgG that competitively blocks the effects of FcγRI on the neuronal surface (Nimmerjahn and Ravetch, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…For example, sensory neurons express high-affinity receptors for IgG (termed FcγRIII) that bind to the Fc region of IgG, particularly in the context of IgG-antigen complexes 58 . Such binding can lead to neuropeptide release by sensory neurons and, in the context of renal reperfusion injury, increased expression of insulin-like growth factor 1 (IGF1), which is protective 59 .…”
Section: Fc Receptorsmentioning
confidence: 99%
“…Next, to assess the role of IGFBP-3 in liver I/R injury, we injected C57BL/6 mice intravenously with 1 × 109 pfu of AdLacZ, AdIGFBP-3, or AdIGFBP-3 GGG virus (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that IGFBP-3 worsened morphometric tissue damage, aminotransferase release, and inflammatory responses with concomitant changes in biochemical parameters following I/R. Of interest, IGF-1 administration protects several organs against I/R injury and improves functional recovery89101112. To exclude the possible involvement of IGF-l, we used an IGFBP-3 mutant with disrupted binding affinity for IGF-1 due to mutations in the binding site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation